Tecnologias de gestão e a qualidade do produto: um estudo em queijarias artesanais de São Rafael - RN - Pereira, Tarciara Magley da Fonseca (Universidade Federal Rural do Semi-Árido, 2015)
Currently the technological progress and competitiveness are factors driving the search for the adoption of quality management programs, these programs bring immediate benefits to organizations. This research has the intention to make an analysis of the current situation in which they are the cheese factories in accordance with the laws on Good Manufacturing Practices, the Ministry of Agriculture, Livestock and Supply (MAPA) in São Rafael/RN. General objective of this research was to analyze the relationship between the management of Good Manufacturing Practices and curd cheese quality produced in São Rafael - RN. The specific objectives are to verify the degree of compliance with Good Manufacturing Practices, the artisan production of curd cheese; Carry out microbiological and physical-chemical analysis, to determine the quality of the cheese curds produced by hand in São Rafael RN; Provide educational material support to enable producers / handlers; Enable producers of Management and Good manufacturing practices and pasteurization of milk to obtain a quality product; Relate the Good Manufacturing Practices with the quality of curd cheese made by hand. This study was descriptive in nature with method of quantitative procedures using check list to carry out the surveys necessary for the proof of the adequacy of standards on Good Manufacturing Practices RDC 275/2002, para microbiological analysis was used to rules Instruction nº 62/2003 of the Ministry of Agriculture, Livestock and Supply and physicochemical analyzes the chestnut methodology (2010). They were invited to participate in the work 07 producers from 07 dairies in São Rafael and settlement Serra Branca II. The choice of the city and the settlement was purposeful need for promoting their products in family farming. This research had as a result the cheese curd with raw milk and without good manufacturing practices is improper for human consumption and that it produced with pasteurized milk by alternative method and with good manufacturing practices, is fit for consumption society. It follows Good Manufacturing Practices should be adopted for a quality product in cheese production facilities in São Rafael
Management technologies and product quality: a study in cheese factories craft of São Rafael RN
Keywords: Cheese curds - quality; Good manufacturing practices; Pasteurization; Family farming; Management; Queijo coalho - qualidade; Boas práticas de fabricação; Pasteurização; Agricultura familiar; Gestão; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE